KEMUDAHAN PENGISIAN SPT, PENGETAHUAN PERPAJAKAN, KUALITAS PELAYANAN PADA KEPATUHAN WPOP DI KPP PRATAMA DENPASAR TIMUR - Rudi Juliantara, I Gede; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2017)
The importance of taxes for financing the country's development demanded taxpayer compliance in order to continue to implement his tax liability that will smooth government activities. Value added tax, knowledge of tax regulations, and the quality of service into the factors that influence taxpayer compliance in tax office on East Denpasar. This study aims to provide empirical of evidence about the effect of the value added tax, knowledge of tax regulations, and the quality of services at the level of an taxpayer. Using 100 with Slovin method. this study using multiple linear regression analysis which is to determine the effect of the independent variable. Results of this study show that value added tax, knowledge of tax regulations, and the quality of service a positive effect on tax compliance intax office on East Denpasar.